A hierarchical approach to improve performance of unstructured peer-to-peer system. (1st January 2012) - Khataniar, G.; Goswami, D.
Unstructured overlays have the disadvantage that queries may take a long time to find required data or it does not guaranty to locate an existing data item. We present an organised network architecture for unstructured peer-to-peer systems where nodes are added to the network in a systematic way to efficiently utilise the node resources. This network architecture is characterised by O (log m n ) network diameter and O (log m n ) messages for node joining and node failure, where n is the number of nodes in the network and m is the number of children of a node. Purely decentralised systems like Gnutella route the query in an environment where the node capabilities are not identified. Whereas the proposed hierarchical unstructured p2p (HUP) routes the query towards the high capable nodes . This organisation of nodes improves the probability of query success rate than that of purely unstructured systems.